2007
DOI: 10.1104/pp.106.092536
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Evolution of the Light-Harvesting Antennae in Chlorophyll a/b-Containing Organisms

Abstract: The light-harvesting complexes (LHCs) of land plants and green algae have essential roles in light capture and photoprotection. Though the functional diversity of the individual LHC proteins are well described in many land plants, the extent of this family in the majority of green algal groups is unknown. To examine the evolution of the chlorophyll a/b antennae system and to infer its ancestral state, we initiated several expressed sequence tag projects from a taxonomically broad range of chlorophyll a/b-conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
185
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(207 citation statements)
references
References 74 publications
15
185
0
3
Order By: Relevance
“…Consistent with this, NPQ in P. patens depends on both PSBS and LHCSR (Alboresi et al, 2010;Gerotto et al, 2011) and presents an active xanthophyll cycle (Alboresi et al, 2008). The analysis of the P. patens genome (Koziol et al, 2007;Alboresi et al, 2008Alboresi et al, , 2011Rensing et al, 2008) revealed that the composition of its antenna system is more similar to that of vascular plants than to unicellular green algae due to the presence of genes encoding LHCb3 and LHCb6, which are not found in Chlamydomonas reinhardtii (Elrad and Grossman, 2004). Both carotenoid accumulation and NPQ are enhanced by abiotic stress Azzabi et al, 2012).…”
Section: Introductionmentioning
confidence: 68%
“…Consistent with this, NPQ in P. patens depends on both PSBS and LHCSR (Alboresi et al, 2010;Gerotto et al, 2011) and presents an active xanthophyll cycle (Alboresi et al, 2008). The analysis of the P. patens genome (Koziol et al, 2007;Alboresi et al, 2008Alboresi et al, , 2011Rensing et al, 2008) revealed that the composition of its antenna system is more similar to that of vascular plants than to unicellular green algae due to the presence of genes encoding LHCb3 and LHCb6, which are not found in Chlamydomonas reinhardtii (Elrad and Grossman, 2004). Both carotenoid accumulation and NPQ are enhanced by abiotic stress Azzabi et al, 2012).…”
Section: Introductionmentioning
confidence: 68%
“…It appears that none of the P. patens Lhcb4 (PpLhcb4; "Pp" for P. patens, hereafter) isoforms are related to AtLhcb4.3 [6], which is found only in dicots and is now classified as Lhcb8 due to its distinct function from AtLhcb4.1 and AtLhcb4.2 [22]. Further, as the ortholog of AtLhcb6 has not been found in green algae so far [11,12], the presence of an AtLhcb6 ortholog in P. patens suggests its uniqueness to land plants, although it is absent in Pinaceae and Gnetales, similar to the case of Lhcb3 [21]. In addition to major and minor LHCIIs, the ortholog of AtLhcb7, which is rarely expressed [22], is present in P. patens [6].…”
Section: Introductionmentioning
confidence: 99%
“…In A. thaliana, Lhcb1, Lhcb2, and Lhcb3 encode major LHCIIs, and Lhcb4, Lhcb5, and Lhcb6 encode minor LHCIIs [10]. In green algae, the genes encoding major LHCIIs are designated as Lhcbm ("m" for major) and have relatively low amino acid sequence similarity to A. thaliana Lhcb1 (AtLhcb1; "At" for A. thaliana, hereafter), AtLhcb2, and AtLhcb3 [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PsbS protein is critical for qE in vascular land plants [32] but its role in green algae is unclear [33] and diatoms apparently do not encode this protein [34]. Conversely, the qE mechanism of eukaryotic algae, for example, Chlamydomonas, relies heavily on the light-harvesting complex stress-related (LHCSR) proteins, which are absent in vascular land plants [34]. State transitions also differ substantially between land plants and algae.…”
Section: Introductionmentioning
confidence: 99%